Immunotherapy and Prevention of Cancer by Nanovaccines Loaded with Whole‐Cell Components of Tumor Tissues or Cells. Issue 43 (18th September 2021) - Ma, Lin; Diao, Lu; Peng, Zuofu; Jia, Yun; Xie, Huimin; Li, Baisong; Ma, Jianting; Zhang, Meng; Cheng, Lifang; Ding, Dawei; Zhang, Xuenong; Chen, Huabing; et al.
Abstract: Tumor tissues/cells are the best sources of antigens to prepare cancer vaccines. However, due to the difficulty of solubilization and delivery of water‐insoluble antigens in tumor tissues/cells, including water‐insoluble antigens into cancer vaccines and delivering such vaccines efficiently to antigen‐presenting cells (APCs) remain challenging. To solve these problems, herein, water‐insoluble components of tumor tissues/cells are solubilized by 8 m urea and thus whole components of micrometer‐sized tumor cells are reasssembled into nanosized nanovaccines. To induce maximized immunization efficacy, various antigens are loaded both inside and on the surface of nanovaccines. By encapsulating both water‐insoluble and water‐soluble components of tumor tissues/cells into nanovaccines, the nanovaccines are efficiently phagocytosed by APCs and showed better therapeutic efficacy than the nanovaccine loaded with only water‐soluble components in melanoma and breast cancer. Anti‐PD‐1 antibody and metformin can improve the efficacy of nanovaccines. In addition, the nanovaccines can prevent lung cancer (100%) and melanoma (70%) efficiently in mice. T cell analysis and tumor microenvironment analysis indicate that tumor‐specific T cells are induced by nanovaccines and both adaptive and innate immune responses against cancer cells are activated by nanovaccines. Overall, this study demonstrates a universal method to make tumor‐cell‐based nanovaccines for cancer immunotherapy and prevention. Abstract : Preventative and therapeutic vaccines can be helpful in preventing and treating cancer. In this work, microsized cancer cells are reassembled into nanosized nanovaccines for cancer immunotherapy and prevention. It is found that such nanovaccines show excellent therapeutic efficacy in melanoma and breast cancer on mice, and can prevent lung cancer (100%) and melanoma (70%) efficiently in mice.